2016
DOI: 10.3892/mco.2016.1044
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of synchronous adenocarcinoma and lymphoma of the stomach: A case report

Abstract: Abstract. Gastric cancer is one of the leading causes of cancer-related mortality worldwide. The majority of gastric cancers are diagnosed at an advanced or metastatic stage, with a 5-year survival rate of ~5-20% and a median overall survival of <1 year. Synchronous occurrence of gastric adenocarcinoma and lymphoma is rare, and thus far there is no consensus regarding their management. We herein describe a case of synchronous gastric adenocarcinoma and diffuse large B-cell lymphoma in a patient with chronic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…Similarly, 57 patients were reported in a review of such cases by Namikawa et al for a study period from 1990 to 2013 in 2014 [ 12 ]. Subsequently, similar individual cases were reported by Weng CH et al in 2016 [ 13 ] and Meng et al in 2019 [ 14 ]. Synchronous primary gastric triple-hit high-grade B-cell lymphoma and gastric adenocarcinoma were reported by Claudia C et al in 2021 [ 15 ], and a case of T-cell lymphoma and gastric adenocarcinoma was reported by Narcisa G et al in 2021 [ 16 ].…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, 57 patients were reported in a review of such cases by Namikawa et al for a study period from 1990 to 2013 in 2014 [ 12 ]. Subsequently, similar individual cases were reported by Weng CH et al in 2016 [ 13 ] and Meng et al in 2019 [ 14 ]. Synchronous primary gastric triple-hit high-grade B-cell lymphoma and gastric adenocarcinoma were reported by Claudia C et al in 2021 [ 15 ], and a case of T-cell lymphoma and gastric adenocarcinoma was reported by Narcisa G et al in 2021 [ 16 ].…”
Section: Discussionsupporting
confidence: 80%
“…1). [12–262] The data were extracted from the abstract in 34 articles, [17,37–39,64,75,76,78,81,94,97,103,129,134,151,162,166,170,174,176,192,195,212,221,222,229,232,234,251,252,256,260–262] of which 21 were in English, 5 in Japanese, 3 in Spanish, 2 in French, 2 in Chinese, and 1 in Czech.…”
Section: Resultsmentioning
confidence: 99%
“…Synchronous multiple primary cancers are defined as two or more tumors occurring within 6 months of each other [7], and among them, synchronous gastric cancer and primary extranodal DLBCL are rare. To the best of our knowledge, 13 cases of synchronous gastric cancer and primary gastric DLBCL and two cases of synchronous gastric cancer and primary small intestinal DLBCL have been reported in English [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Particularly, the patient in this case report is the first reported case of synchronous gastric cancer and primary adrenal DLBCL in the English literature.…”
Section: Discussionmentioning
confidence: 99%